Pengembangan Video Animasi Pembelajaran Berbasis Kearifan Lokal terhadap Peningkatan Motivasi Belajar Peserta Didik pada Materi Gerak Lurus - Muhammad Samsul Hadi; Mustain Shogir; Baiq Aryani Novianti; Sapiruddin (Mataram University, 2025)
This study aimed to: (1) develop a local wisdom-based animated learning video to enhance students’ learning motivation on the topic of linear motion, and (2) determine the feasibility and practicality of the developed animated learning video. This research employed the 4D development model, which consists of four stages: Define, Design, Develop, and Disseminate. The subjects involved in the product evaluation were three material experts, three media experts, three physics teachers, and 15 tenth-grade students of MA Hizbul Wathan NWDI Semaya. Data were collected using questionnaires that had been previously validated. The results of data analysis and discussion indicated that the product was highly feasible and highly practical. The feasibility and practicality were reflected in the average scores obtained from media experts (92.91%), material experts (86.85%), subject teachers (93.94%), and student responses (92.12%). Based on these percentages, the animated learning video was categorized as highly feasible and highly practical for use in the learning process.